2021
DOI: 10.1080/23802359.2021.1972049
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome of a rare and endangered plant species Phalaenopsis zhejiangensis: genomic features and phylogenetic relationship within Orchidaceae

Abstract: Phalaenopsis zhejiangensis is a rare and endangered plant species with extremely small populations. The complete chloroplast (cp) genome of P. zhejiangensis was assembled, its structural organization was described and comparative genomic analyses was carried out. The cp genome of P. zhejiangensis is 143,547 bp in length, with a GC content of 37.2%, which includes a pair of inverted repeats (IRs) of 24,464 bp separated by a small single-copy region of 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The ndings from the phylogenetic analysis did not align with numerous prior researches, which have established that P. wilsonii and P. lowii comprise a sister group [23,24,27]. Jiang et al (2021) concluded that P. zhejiangensis was most closely related to P. wilsonii [25]. However, another study has shown that P. wilsonii and P. stobartiana were most closely related, and the clade containing these two species was most closely related to the clade containing P. zhejiangensis and P. lowii [26].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The ndings from the phylogenetic analysis did not align with numerous prior researches, which have established that P. wilsonii and P. lowii comprise a sister group [23,24,27]. Jiang et al (2021) concluded that P. zhejiangensis was most closely related to P. wilsonii [25]. However, another study has shown that P. wilsonii and P. stobartiana were most closely related, and the clade containing these two species was most closely related to the clade containing P. zhejiangensis and P. lowii [26].…”
Section: Discussionmentioning
confidence: 71%
“…Complete chloroplast genomes have been extensively applied to taxonomic studies and phylogeny reconstruction of plants [15,16,17]. Several chloroplast genomes of Phalaenopsis plants have been sequenced, including Phalaenopsis Aphrodite [18], Phalaenopsis 'Tiny Star' [19], Phalaenopsis lowii [20], Phalaenopsis lobbii [21], Phalaenopsis mannii [22], P. wilsonii MW194929 [23], P. wilsonii NC_057488 [24], Phalaenopsis zhejiangensis [25], Phalaenopsis stobartiana [26], and Phalaenopsis malipoensis [27]. No complete chloroplast genome sequences of P. wilsonii f. wilsonii and P. braceanum have been uploaded to the National Center for Biotechnology Information (NCBI) database.…”
Section: Introductionmentioning
confidence: 99%
“…The previous reports have indicated a relatively limited number of polymorphic SSR markers for the Aeridinae subtribe collection. The previously reported genetic analysis for the Aeridinae subtribe using molecular markers includes those reported by Yun et al ( 2020) for the genetic diversity of P. scolopendrifolia, Kim et al (2020) for the evolution and phylogenetics of the Aeridinae subtribe, Dwiati and Susanto (2021) for the intergeneric crosses between the genus Phalaenopsis and Vanda, and Jiang et al (2021) for the chloroplasts genomic of the Phalaenopsis zhejiangensis.…”
Section: Ssr Polymorphism and Genetic Diversitymentioning
confidence: 98%